Plant Growth-Promoting Bacteria: Biological Tools for the Mitigation of Salinity Stress in Plants - Kumar, Akhilesh; Singh, Saurabh; Gaurav, Anand Kumar; Srivastava, Sudhakar; Verma, Jay Prakash (Frontiers in Microbiology, 2020)
Salinity stress is one of the major abiotic stresses threatening sustainable crop production worldwide. The extent of salinity affected area is expected to cover about 50% of total agricultural land by 2050. Salinity stress produces various detrimental effects on plants’ physiological, biochemical, and molecular features and reduces productivity. The poor plant growth under salinity stress is due to reduced nutrient mobilization, hormonal imbalance, and formation of reactive oxygen species (ROS), ionic toxicity, and osmotic stress. Additionally, salinity also modulates physicochemical properties and reduces the microbial diversity of soil and thus decreases soil health. On the other hand, the demand for crop production is expected to increase in coming decades owing to the increasing global population. Conventional agricultural practices and improved salt-tolerant crop varieties will not be sufficient to achieve the yields desired in the near future. Plants harbor diverse microbes in their rhizosphere, and these have the potential to cope with the salinity stress. These salinity-tolerant plant growth-promoting bacteria (PGPB) assist the plants in withstanding saline conditions. These plant-associated microbes produce different compounds such as 1-aminocyclopropane-1-carboxylate (ACC) deaminase, indole-3-acetic acid (IAA), antioxidants, extracellular polymeric substance (EPS), and volatile organic compounds (VOC). Additionally, the naturally associated microbiome of plants has the potential to protect the host through stress avoidance, tolerance, and resistance strategies. Recent developments in microbiome research have shown ways in which novel microbe-assisted technologies can enhance plant salt tolerance and enable higher crop production under saline conditions. This focused review article presents the global scenario of salinity stress and discusses research highlights regarding PGPB and the microbiome as a biological tool for mitigation of salinity stress in plants.